Burkina Faso : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2004)
This Report on the Observance of Standards and Codes Data Module provides a review of Burkina Faso's data dissemination practices against the IMF's general data dissemination system, complemented by an in-depth assessment of the quality of national accounts, consumer price, government finance, monetary, and balance of payments statistics. Delays in implementation and lack of resources have left the statistical system fragmented and vulnerable. The national statistics coordination council has failed to fulfill its mandate for lack of adequate technical support.